A synchrophasor measurement based wide-area power system stabilizer design for inter-area oscillation damping considering variable time-delays - Prakash T.; Singh V.P.; Mohanty S.R. (My University, 2025)
Owing to the everlasting growth of power demand and continual change in configuration of modern power system, the role of electric utility in supplying secure and reliable power has become more prominent. Presently, the ongoing interconnections of existing power system are adding more complexity to the system and consequently, making it exposed to small-signal stability issues related to inter-area oscillations. If these issues are not adhered efficiently then it may lead to system voltage collapse and even blackouts. However, incorporation of a properly designed power system stabilizer (PSS) based on information received from wide-area measurements can solve the problem. Moreover, design of such PSS is still a challenging task as the network uncertainties are highly unpredictable. The remote signals obtained through wide-area measurement system (WAMS) are needed to be transferred to control center via communication channel. However, this process makes the system subjected to inherent communication time-delays. Consequently, the performance of PSS using these signals may deteriorate if these delays are not compensated appropriately. This motivated the present work of the design of wide-area power system stabilizer (WAPSS) utilizing information contained in synchrophasor measurements for inter-area oscillation damping considering variable communication time-delays. To obtain wide-area synchrophasor measurements, phasor measurement units (PMUs) compliant to IEEE C37.118.1 principles are adopted. The variability in communication time-delays are compensated by a time-delay compensator (TDC) designed using Simevents toolbox available with MATLAB. Based on geometric measures of controllability and observability, the choice of location of WAPSSs and the selection of their respective input signal are obtained. The parameters of WAPSSs are tuned by recently proposed, simple yet efficient, Jaya algorithm (JA). Different case studies of small-signal analysis and nonlinear time-domain simulations are carried out on New England 39-bus test system operating under diverse conditions. The obtained results establish the achievement of desired performance by the JA based WAPSSs regarding inter-area oscillation damping under consideration of variable communication time-delays. © 2018 Elsevier Ltd